The Progressive Potential of Local Social Policy Activism - Marquardt, Richard (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2008)
A local network of progressive activists can make a significant difference to social policyoutcomes, even when regressive policy currents prevail at other scales of the state. This isthe conclusion to a case study of the struggle in Ottawa over welfare reform during MileHawis's Common Sense Revolution in Onturio. Much of the literature on this topic stressesthe regressive nuture of the mend toward downloading of social programs to local governmentsduring the 1990s. This position is valid but tends to obscure the potential of effortsat the local scale to achieve propessive social policies. In this case, a local anti-povertynetwork, by working with and within the local government and community-based organizations,successfully resisted some of the most regressive aspects of the welfare reformagenda of the Harris government and created a set of services that responded well to theneeds of the majority of social assistance recipients. This case highlights the multiscalar natureof the social policy process and of the key role played in the implementation phase of thatprocess by actors at the local scale. It also alerts us to the possibility that progressive policynetworks can run through branches of the state. Community-based activists should recognizethat they may have allies at City Hall, both among the elected councillors and the stuff of itsdepartments. A t the same time, prog~essivea ctors inside the local state need to nurture thoseinstitutions in the community that provide the material base for progressive social movements.Un rbeau local d'activistes progressistes peut avoir une influence conside'rable sur l'issuedes politiques sociales, m&me si une ide'ologie re'trograde en mati2re de politiques pre'vaut h d'autres niveaux au sein de l ' ~ t a tC. 'est la conclusion tire'e d'une e'tude de cas portant surle combat men6 h Ottawa contre la re'forme de l'assistunce sociale mise en Euwe dans lecadre de la Re'volution du bon sens du gouvernement de Mike Harris, en Ontario. Unebonne partie de la documentation sur ce theme insiste sur la nature re'nograde de latendunce h transfe'rer la responsabilite' des programmes sociaux aux administrationsmunicipales qui a caracte'rise' les anne'es 1990. Cette position est ualide, mais elk tend hmasquer le potentiel des efforts &ploye's par le secteur local pour mettre en place des politiquessociales progressistes. Dans le cas e'voque' ici, un re'seau antipauvrete' local, encollaborant et en s'inuestissant avec l'administration municipale et les organismes communautaires,a combattu avec SUCC~S certuins des aspects les plus re'trogrades de la re'formede l'aide sociale du gouvernement Harris et mis sur pied un ensemble de services qui are'pondu eficacement aux besoins de la majorite' des prestataires. Ce cas particulier meten lumiere la nature multiscalaire du processus d'e'laboration des politiques sociales etle r6le cle' joue' h l'e'tape de leur mise en oeuvre par les acteurs locaux. 11 nous sensibiliseigalernent h la possibilite' pour les rbeaux progressistes en mutiere de politiques d'agirau sein des filieres de l ' ~ t a tL. es activistes communautaires devraient re'aliser qu'ils ontpeut-&tre des allib h l'h6tel de ville, tant pami les conseillers municipaux que chez lesemployis des divers services. Parall2lement, les interwenants progressistes au sein de cesadministrations locales doivent alimenter les institutions qui fournissent h la communaute'les fondements mate'riels des mouvements sociaux progressistes.